Pengaruh Karakteristik Pekerjaan terhadap Kepuasan Kerja melalui Komitmen Organisasi (Studi pada Karyawan Bank Wilayah Surabaya) - Dicky Januardi; Budiono Budiono (Jurnal Ilmu Manajemen, 2021)
This research aims to evaluate and analyze job characteristics towards job satisfaction through organizational commitment in the Surabaya region's bank employees. This research is quantitative. A sample of 72 respondents with a saturated sample technique through an online questionnaire. Statistical analysis using Partial Least Square (PLS) with SmartPLS software version 3.0. This study concluded that job characteristics were not significant to job satisfaction. Positive and significant work characteristics of organizational commitment. Positive and significant organizational commitment to job satisfaction. Organizational commitment manages to mediate the relationship between job characteristics and job satisfaction